Montessori Method in Character Education: Analysis of the Effectiveness of the Montessori Method in Character Education in Early Childhood Education - Shelly Yulia; Tri Joko Raharjo; Fakhruddin Fakhruddin; Ali Formen (International Conference on Science, Education, and Technology, 2022)
Abstract. Character education for early childhood is intended to instill moral values that are useful in successful learning at the next level of education and become good habits when they are adults. Character that has been formed from an early age will affect the appreciation and practice throughout children life. In educational practice of early childhood education, however, the learning methods used are often less focused on developing character education than the development of cognitive academic abilities. As a result, early childhood education produces students who have high cognitive abilities but are not balanced with good character. This study aims to describe and test the effectiveness of Montessori method in character education in early childhood education using descriptive research method. The objects are teachers at early childhood education institutions involving 112 respondents. The results show that Montessori Method-based learning that emphasizes the importance of independence and self-improvement activities in building life skills to improve students’ intellectual abilities has proven effective in early childhood character education.